1983
DOI: 10.1093/jn/113.12.2485
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Balance Studies in Young Men to Assess the Protein Quality of an Isolated Soy Protein in Relation to Meat Proteins

Abstract: The protein nutritional value of an isolated soy protein was examined in healthy young men during 10-day N-balance periods. In the first study (expt 1), 10 young men received a diet providing a test protein (N X 6.25) intake of 0.6 g protein per kilogram per day with nitrogen from either lean beef, isolated soy protein or various combinations of the two sources. No differences in N balance, digestibility or net protein utilization were observed when the soy protein replaced beef. In the second study (expt 2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 11 publications
1
20
1
1
Order By: Relevance
“…Instead, despite high protein quality ( Fig. 1) [45][46][47][48][49][50], the digestion rate of proteins (e.g. whey and casein as well as soy protein) influences protein turnover and how amino acids support protein synthesis in central versus peripheral tissues [51][52][53][54].…”
Section: Differences In 'High-quality' Proteins and The Support Of Mumentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, despite high protein quality ( Fig. 1) [45][46][47][48][49][50], the digestion rate of proteins (e.g. whey and casein as well as soy protein) influences protein turnover and how amino acids support protein synthesis in central versus peripheral tissues [51][52][53][54].…”
Section: Differences In 'High-quality' Proteins and The Support Of Mumentioning
confidence: 99%
“…NPU for casein and whey from reference [49]. NPU for soy from reference [50]. , casein; , whey; , soy.…”
Section: Differences In 'High-quality' Proteins and The Support Of Mumentioning
confidence: 99%
“…Preparation of the SPLC Products of soybean in combination with products of animal origin can be successfully applied to improve the nutritional and biological value of food concentrates for diets in extreme conditions (Bojcova et al, 2011;Kalenik et al, 2012;Wayler et al, 1983). The results of numerous studies have shown that extraction from germinated soybean seeds is the most preferable option, from the standpoint of preparation and isolation of protein substances, due to the positive effects of germination on reduction of the content of anti-nutritional substances (trypsin inhibitors, the Bowman-Birk, urease), the increase in the content of mineral substances and vitamins and removal of the shell (Bau et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the agenda of the next FAO/WHO/UN University meeting in 1981 was set and the report (Food & Agriculture Organization/World Health Organization/United Nations University, 1985), on the basis of both short-and long-term balance data, duly raised the safe allowance to 0·75 g/kg per d. This value was adopted by national bodies around the world. Apart from N-balance studies on the elderly (Gersovitz et al 1982) following up earlier work (Uauy et al 1978a) and a major series of studies on the nutritional value of soyabean protein (Istfan et al 1983a,b;Scrimshaw et al 1983;Wayler et al 1983;Young et al 1984), the early 1980s were to mark the end of Young's N-balance studies aimed at the adult protein requirement. The magnitude of this part of his work is apparent from his recent meta-analysis of all published data on adults (Rand et al 2003), used as the basis of the recent US dietary reference intakes report on protein requirements (Institute of Medicine, 2002).…”
Section: Defining Protein Requirementsmentioning
confidence: 99%